Serum Levels of Tissue Inhibitors of Metalloproteinase 2 in Patients With Systemic Sclerosis With Duration More Than 2 Years: Correlation With Cardiac and Pulmonary Abnormalities - Amira Shahin; Amani Elsawaf; Shahira Ramadan; Olfat Shaker; Mona Amin; Mohamed Taha (Hindawi Limited, 2006)
In this study, we measured the serum concentration of TIMP-2 in patients with systemic sclerosis (SSc) and explored its possible correlation with cardiac and pulmonary lesions. We studied 42 patients with SSc, with duration equal to or more than 2 years. CT chest, ECG, echocardiography, and serum TIMP-2 concentration measurement using ELISA technique were performed in all patients and in 25 normal controls. The mean serum levels of TIMP-2 in patients was higher than in controls (P=.005). The mean CT score of dSSc patients with elevated TIMP-2 levels was significantly higher than dSSc patients with normal levels (P=.013). Four patients out of five with elevated TIMP-2 levels showed diastolic dysfunction (80%), compared to 2 out of 15 lSSc patients with normal levels (13.3%), with P=.014. Our research, though involving a small group of patients, points to the probable role of TIMP-2 in the development of pulmonary lesions in dSSc patients and cardiac lesions in lSSc patients with duration equal to or more than 2 years.